Small-Molecule TLR8 Antagonists via Structure-Based Rational Design. Issue 10 (18th October 2018) - Hu, Zhenyi; Tanji, Hiromi; Jiang, Shuangshuang; Zhang, Shuting; Koo, Kyoin; Chan, Jean; Sakaniwa, Kentaro; Ohto, Umeharu; Candia, Albert; Shimizu, Toshiyuki; Yin, Hang
Summary: Rational design of drug-like small-molecule ligands based on structural information of proteins remains a significant challenge in chemical biology. In particular, designs targeting protein-protein interfaces have met little success given the dynamic nature of the protein surfaces. Herein, we utilized the structure of a small-molecule ligand in complex with Toll-like receptor 8 (TLR8) as a model system due to TLR8's clinical relevance. Overactivation of TLR8 has been suggested to play a prominent role in the pathogenesis of various autoimmune diseases; however, there are still few small-molecule antagonists available, and our rational designs led to the discovery of six exceptionally potent compounds with ∼picomolar IC50 values. Two X-ray crystallographic structures validated the contacts within the binding pocket. A variety of biological evaluations in cultured cell lines, human peripheral blood mononuclear cells, and splenocytes from human TLR8-transgenic mice further demonstrated these TLR8 inhibitors' high efficacy, suggesting strong therapeutic potential against autoimmune disorders. Graphical Abstract: Highlights: CU-CPTs successfully target an unconventional pocket on a protein-protein interface Highly potent and selective CU-CPT provided useful tools in studying TLR8 signaling CU-CPT9 derivatives demonstrated promising therapeutic potentials Abstract : Structure-based rational design led to discovery of six exceptionally potent compounds with ∼pM IC50 values. Two new X-ray crystallographic structures validated the contacts within the binding pocket. TLR8-transgenic mice further demonstrated these TLR8 inhibitors' high efficacy, suggesting strong therapeutic potential against autoimmune disorders.